2022
DOI: 10.3389/fphar.2022.1036013
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone protects skin cells from ultraviolet radiation-induced photoaging via its antioxidant effect and by reducing mitochondrial dysfunction and inhibiting apoptosis

Abstract: The integrity of skin tissue structure and function plays an important role in maintaining skin rejuvenation. Ultraviolet (UV) radiation is the main environmental factor that causes skin aging through photodamage of the skin tissue. Cryptotanshinone (CTS), an active ingredient mianly derived from the Salvia plants of Lamiaceae, has many pharmacological effects, such as anti-inflammatory, antioxidant, and anti-tumor effects. In this study, we showed that CTS could ameliorate the photodamage induced by UV radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 95 publications
0
10
0
4
Order By: Relevance
“…The overexposure of normal skin to solar UVR may give rise to short-term reactions such as erythema and atypical pigmentation, and long-term responses increasing a risk factor of developing photoaging and skin disorders [ 20 ]. Chronological aging in human skin, like photoaging is a cumulative biological process, which leads to the evolutionary modification of structural and functional features [ 21 ]. UVR activates a complex biochemical signaling cascade involving oxidative stress and inflammatory response [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overexposure of normal skin to solar UVR may give rise to short-term reactions such as erythema and atypical pigmentation, and long-term responses increasing a risk factor of developing photoaging and skin disorders [ 20 ]. Chronological aging in human skin, like photoaging is a cumulative biological process, which leads to the evolutionary modification of structural and functional features [ 21 ]. UVR activates a complex biochemical signaling cascade involving oxidative stress and inflammatory response [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive UVB radiation induces skin cells to undergo apoptosis, ultimately leading to skin inflammation [83].The NF-κB signaling pathway plays an essential role in the transcriptional regulation of various genes involved in cell growth, survival, proliferation, apoptosis, adhesion, migration, carcinogenesis, and inflammation [84]. Studies reported that UVB radiation activates NF-κB in BALB/c mouse skin at post-irradiation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Cryptotanshinone (CTN) is a diterpenoid monomer and a lipophilic component extracted from the dried roots and rhizomes of the traditional Chinese herb S. miltiorrhiza ( Li et al, 2021 ; Zhang et al, 2023 ). CTN has been proven to possess various biological activities, including antioxidant ( Guo et al, 2022 ), anti-tumor ( Dalil et al, 2022 ), antibacterial ( Zhong et al, 2021 ), and anti-inflammatory effects ( Wu et al, 2020 ). Li ( Popa et al, 2021 ) discovered that CTN effectively suppresses NSCLC cells invasion, proliferation and tumorigenesis.…”
Section: Natural Products Modulating Ferroptosis For Intervention In ...mentioning
confidence: 99%